Anti-biofilm property of essential oils from Cymbopogon sp. against pathogenic bacteria in single-culture and co-culture - Millezi, Alessandra Farias; Schuh, Vanessa; Schuh, Janaina; Amaral, Taciara Penno do (Ciência e Natura, 2020)
In this study, we evaluated whether the essential oils (EOs) from Cymbopogon flexuosus and Cymbopogon martinii can prevent production of biofilms either in single or combined culture of Staphylococcus aureus and Pseudomonas aeruginosa. Biofilm formation was assessed by microtiter-plate test with further quantification of viable cells and biofilm biomass. The evaluated EOs at 0.78 % significantly (P < 0.05) reduced only the viable cells of S. aureus that inhabited biofilm. However, in single-and co-culture assays, both oils significantly (P > 0.05) decreased the amount of biofilm biomass. Biofilm reductions between 52-83% and 60-93% were achieved for the treatments with EOs from C. flexuosus and C. martinii, respectively. Although the biomass reductions of simgle and co-cultivated biofilms were significant, the same was not true for viable cells, except for S. aureus. Considering that the remaining colony forming units can reconstitute the EPS matrix, studies with higher concentrations than those used in this research are suggested in order to obtain greater logarithmic reductions of viable bacterial cells.